ANALISIS RAGAM PRODUK DAN KUALITAS INFORMASI TERHADAP MINAT BERBELANJA DISITUS ONLINE STORE SHOPEE (STUDI PADA PT REYCOM DOCUMENT SOLUSI DI JAKARTA) - Arif Miharja; Danu Adi Kurniawan; Dian Maolani; Darrinh Rosharia (Aliansi : Jurnal Manajemen dan Bisnis, 2021)
The title of this research is Analysis of Product Variety and Quality of Information on Shopping Interests on the shopee online store site (Study on Employees of PT Reycome Document Solusi in Jakarta). Does the variety of products and quality of information affect the interest in shopping at the Shopee online store site? The purpose of this study was to determine the Analysis of Product Variety and Quality of Information on Shopping Interests.The population in this study were online users, namely employees of PT Reycome Document Solusi in Jakarta who had made purchases on the online Store Shopee site. According to the opinion of the roots, the sample requirements used in this study were 64 people. This research is an associative study using a quantitative approach. This research is categorized as survey research, in which the research instrument is a questionnaire. Validity test using CFA (Confirmatory Factor Analysis Model), using the SPSS application. The results of this study indicate that Product Variety has no significant effect on Shopping Interest on Shopee's online store site with test results (t) of 0.970 greater than 0.05, and information quality has a significant effect on Shopping Interest on Shopee's online store sites with test results (t) of 0.003 is less than 0.05. Thus the Information Quality variable (X2) is the most dominant variable influencing the shopping interest on the Shopee online store site.